Maternal death in women with epilepsy: Smaller scope studies. (30th October 2018) - Christensen, Jakob; Vestergaard, Claus; Hammer Bech, Bodil
Abstract : Objective: To determine the maternal mortality in women with epilepsy. Methods: This was a matched case-control study of pregnant women in Denmark who were born in Denmark between January 1, 1962, and December 31, 1994, and who were alive on their 18th birthday. We defined maternal mortality as deaths in pregnancy and the first 42 days after termination of pregnancy. Cases were pregnancies in women with a diagnosis of epilepsy before the termination of pregnancy. Data were analyzed with a conditional logistic model. For comparison, we estimated the mortality in women of childbearing age (18–50 years) diagnosed with epilepsy regardless of pregnancy status using a Poisson model. Results: We identified 2, 105, 084 pregnancies, including 11, 976 (0.57%) pregnancies in which the mother was diagnosed with epilepsy. Of the 176 maternal deaths in this cohort, 5 women had a diagnosis of epilepsy. The mortality associated with an epilepsy diagnosis was >5 times higher compared to the mortality in women without this diagnosis (odds ratio 5.57, 95% confidence interval 2.23–13.9, p < 0.001). Conclusions and Relevance: Maternal mortality in women with epilepsy in Denmark was lower than what has previously been reported from United States and the United Kingdom. However, the maternal mortality in women with epilepsy was considerably higher compared to women without epilepsy. Further studies should address whether improving epilepsy care in women with epilepsy could reduce the rate of maternal deaths.